Television views and readings from stall holders about Rafael Correa’s presidential speech - Andino Veloz, Byron (2019)
This text presents the reception study’s results on the senses produced in vendors, which are located in La Ofelia Public Market, at Northern Quito, over the presidencial speech of the Ecuadorian president, Rafael Correa. This investigation analyzed the dominant/hegemonic, negotiated and oppositional positions of vendors over the presidential speech. In addition, it investigated how the sense was produced in vendors as an interpretative community. This process is involved in building political identities. This text also reflects the social mediations on vendors of that fair, as a subaltern group, wich is an interpretive community. With interviews and a viewing of Correa speech was obtained the readings on the presidential speech